Evaluating opportunities for advancing the use of alternative methods in risk assessment through the development of fit-for-purpose in vitro assays. (April 2018) - McMullen, Patrick D.; Andersen, Melvin E.; Cholewa, Brian; Clewell, Harvey J.; Dunnick, Katherine M.; Hartman, Jessica K.; Mansouri, Kamel; Minto, Melyssa S.; Nicolas, Chantel I.; Phillips, Martin B.; Slattery, Scott; Yoon, Miyoung; et al.
Abstract: An evolving regulatory, scientific, and legislative landscape is driving a fundamental change in how chemical safety decisions are made. As we move to implement changes, regulatory agencies and industry are beginning to adopt tiered approaches, which leverage high-throughput screening technologies for prioritization and read across, followed by interrogation of "hit chemicals" with more rigorous dose-response assessment either in fit-for-purpose human cell-based assays or with traditional in vivo tests. However, to date, suitable in vitro alternatives do not exist for the vast majority of the organ toxicities that form the basis of current regulatory decisions. To successfully support safety decisions, biologically relevant, quantitative, cell-based assays that evaluate dose-response and identify regions of safety for chemical exposure are required. This review evaluates the current state of the science in the development of such assays, identifies key gaps in the current tests, and recommends areas where research efforts may be focused to help move the risk assessment community towards more wide-spread use of in vitro methods. Our analysis suggests that a key shortcoming in the current efforts is the ability to test volatile compounds and to predict pulmonary toxicity. We present a mechanistically-based path forward for the development of a fit-for-purpose lung toxicity assay. Highlights: Evaluated regulatory landscape to identify opportunities for broader use of alternatives US government agency databases were mined to identify common critical effects. In vitro methods were evaluated to identify weaknesses in current assay coverage. Screening efforts have difficulty identifying bioactivity of volatile compounds. We propose characteristics of a successful assay for pulmonary toxicity.